Antakng as a Unit of Value in the Life of Dayak Benuaq Tonyooi Community in West Kutai - Kalista, Valenci; Saka, Putri Ananda; Sheikhi, Mohammad (IAS Journal of Localities, 2024)
This paper aims to explain the shift that has occurred in antakng as a customary value standard in the Dayak Benuaq Tonyooi community. Using a qualitative approach through in-depth interviews, observations, and document studies, this research was conducted in West Kutai Regency, East Kalimantan. The results showed that antakng, which has traditionally served as ceremonial object and used as a unit of value for Dayak people, and also functions as a standard of exchange, has now been replaced and converted into a unit of currency (rupiah). Currently, the value of 1 antakng is equivalent to IDR 400,000 (four hundred thousand rupiah). This transformation occurred due to the scarce availability of antakng (urns) and as a form of rational choice from the community to continue conducting economic transactions and maintaining customary practices in the midst of changing times. Antakng converted to money or rupiah is now used as the unit of value for paying wages and fines, and is applied in the settlement of cases in West Kutai. This research recommends the need for preservation efforts and the establishment of clear regulations regarding the use of antakng in the customary context, in order to preserve traditional values amid the challenges of modernization.